Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1088/0031-9155/56/3/019
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study of irregular respiratory motion and its dosimetric impact on lung tumors

Abstract: This study is aimed at providing a dosimetric evaluation of the irregular motion of lung tumors due to variations in patients' respiration. Twenty-three lung cancer patients are retrospectively enrolled in this study. The motion of the patient clinical target volume is simulated and two types of irregularities are defined: characteristic and uncharacteristic motions. Characteristic irregularities are representative of random fluctuations in the observed target motion. Uncharacteristic irregular motion is class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…The proposed methodology for irregular breathing classification can impact the dose calculation for patient treatments [9], [10]. The highly irregularly breathing patient may be expected to have a much bigger internal target volume (ITV) than a regular one, where ITV contains the macroscopic cancer and an internal margin to take into account the variations due to organ motions [9].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed methodology for irregular breathing classification can impact the dose calculation for patient treatments [9], [10]. The highly irregularly breathing patient may be expected to have a much bigger internal target volume (ITV) than a regular one, where ITV contains the macroscopic cancer and an internal margin to take into account the variations due to organ motions [9].…”
mentioning
confidence: 99%
“…The highly irregularly breathing patient may be expected to have a much bigger internal target volume (ITV) than a regular one, where ITV contains the macroscopic cancer and an internal margin to take into account the variations due to organ motions [9]. Thus, the detection of irregular breathing motion before and during the external beam radiotherapy is desired for minimizing the safety margin [10]. Only a few clinical studies, however, have shown a deteriorated outcome with increased irregularity of breathing patterns [1], [8], [10], probably due to the lack of technical development in this topic.…”
mentioning
confidence: 99%
See 3 more Smart Citations